Influence of Fundamental Factors to Share Price in Property, Real Estate, and Construction Companies - Faradiba Utari Kuswardani; Suwinto Johan (Universitas Tarumanagara, 2022)
In recent years there is a rapid growth in users or investors in the capital market. The rapid growth of technology is also one of many reasons investors can enter the capital market easily. This research was conducted to help the new investor in collecting important information about certain companies, especially Property, Real Estate, and Construction sectors. The objective of this research is to test and investigate the impact of Debt Ratio (D/R), Price Earnings Ratio (P/ER), and Return on Assets (ROA). This research is also to compare and improve the results of prior research. The sample used was Property, Real Estate, and Construction companies that passed the test of purposive sampling. Three years of data have been used (2017 to 2019). The Descriptive statistics and Normality found that the data were normally distributed with a random effect model to test the hypotheses. Regression results show that the Price Earning Ratio (P/ER) influences Market Price. While the Debt Ratio (D/R) and Return on Assets (ROA) of the companies were not influencing toward Market Price. Dalam beberapa tahun terakhir terjadi pertumbuhan yang pesat pada pengguna atau investor di pasar modal. Pertumbuhan teknologi yang pesat juga menjadi salah satu alasan investor dapat memasuki pasar modal dengan mudah. Penelitian ini dilakukan untuk membantu investor baru dalam mengumpulkan informasi penting tentang perusahaan tertentu khususnya sektor Properti, Real Estate dan Konstruksi. Penelitian ini bertujuan untuk menguji dan mengetahui pengaruh Debt Ratio (D/R), Price Earnings Ratio (P/ER) and Return on Assets (ROA). Penelitian ini juga untuk membandingkan dan menyempurnakan hasil penelitian sebelumnya. Sampel yang digunakan adalah perusahaan Properti, Real Estate dan Konstruksi yang lolos uji purposive sampling. Data tiga tahun telah digunakan (2017 hingga 2019). Statistik deskriptif dan normalitas menemukan bahwa data terdistribusi normal dengan model efek acak untuk menguji hipotesis. Hasil regresi menunjukkan bahwa Price Earning Ratio (P/ER) berpengaruh terhadap Harga Pasar. Sedangkan Debt Ratio (D/R) and Return on Assets (ROA) perusahaan tidak berpengaruh terhadap Harga Pasar